2017
DOI: 10.1104/pp.17.00697
|View full text |Cite
|
Sign up to set email alerts
|

RopGEF1 Plays a Critical Role in Polar Auxin Transport in Early Development

Abstract: Polar auxin transport, facilitated by the combined activities of auxin influx and efflux carriers to maintain asymmetric auxin distribution, is essential for plant growth and development. Here, we show that Arabidopsis (Arabidopsis thaliana) RopGEF1, a guanine nucleotide exchange factor and activator of Rho GTPases of plants (ROPs), is critically involved in polar distribution of auxin influx carrier AUX1 and differential accumulation of efflux carriers PIN7 and PIN2 and is important for embryo and early seedl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 59 publications
0
35
1
Order By: Relevance
“…In leaf pavement cells, the auxin-activated interaction of ROP2 with RIC4 inhibits PIN endocytosis by stabilizing cortical actin filaments, whereas the RIC4-dependent assembly of cortical F-actin promotes lobe outgrowth [53]. Recently, we showed that a Rho of plants (Rop)-guanine nucleotide exchange factor, RopGEF1, regulates the polarized localization of AUX1 and affects the distribution of PIN7 and PIN2 [27]. Recently, we showed that a Rho of plants (Rop)-guanine nucleotide exchange factor, RopGEF1, regulates the polarized localization of AUX1 and affects the distribution of PIN7 and PIN2 [27].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In leaf pavement cells, the auxin-activated interaction of ROP2 with RIC4 inhibits PIN endocytosis by stabilizing cortical actin filaments, whereas the RIC4-dependent assembly of cortical F-actin promotes lobe outgrowth [53]. Recently, we showed that a Rho of plants (Rop)-guanine nucleotide exchange factor, RopGEF1, regulates the polarized localization of AUX1 and affects the distribution of PIN7 and PIN2 [27]. Recently, we showed that a Rho of plants (Rop)-guanine nucleotide exchange factor, RopGEF1, regulates the polarized localization of AUX1 and affects the distribution of PIN7 and PIN2 [27].…”
Section: Discussionmentioning
confidence: 99%
“…F3 seedlings were subjected to further experimentation, with the marker plants as controls. Quantification of the seedling F-actin density was performed as described by Liu et al [27] and according to the methods of Dyachok et al [28] and Higaki et al [29]. The density of F-actin was defined as the ratio of the filament occupancy and cell area, as described by Dyachok et al [28].…”
Section: B-glucuronidase (Gus) Activity Assaymentioning
confidence: 99%
See 2 more Smart Citations
“…Arabidopsis has 14 RopGEFs in its genome, with a high degree of sequence similarity [8,9]. Functional studies showed that AtRopGEF1 and AtRopGEF4 specifically regulate ROP11 in abscisic acid (ABA)-mediated stomatal closure [10], and that AtRopGEF1 plays a role in controlling lateral root growth [11] and polar auxin transport to achieve cell polarity during early plant development [12]. Among them, seven members are specifically or highly expressed in pollen tubes and function redundantly [8,13].…”
mentioning
confidence: 99%